Effect of immunoadjuvants on the disease course in patients with operable breast cancer - M. M. Vasilyeva; I. P. Moshurov; L. Yu. Grivtsova; N. N. Tupitsyn; N. A. Kozlov; M. B. Vasilyev (ABV-press, 2019)
Background. A new strategy of breast cancer management is required for effective disease prevention and control. Immunotherapy is one of promising options.Objective: to evaluate the effect of immunoadjuvant polyoxidonium on pathmorphological changes in breast tumors.Materials and methods. The study was performed in 75 patients with breast cancer: 50 patients received polyoxidonium in a neoadjuvant regimen (main group), 25 patients did not receive polyoxidonium (control group). Polyoxidonium at a dose of 12 mg was administered intramuscularly 1 time per day on the days 1, 2, 3, 5 and 7 before surgery; on the day 8, radical mastectomy was performed in patients of both groups, followed by histological examination and determination of the grade of therapeutic pathomorphosis of the tumor.Results. The proportion of cases with grade I therapeutic pathomorphosis was 58 %, grade II therapeutic pathomorphosis - 6 %. Pathomorphosis in metastatic lymph nodes was observed in 22.7 % of cases.Conclusion. The anti-tumor effect of polyoxidonium was confirmed on the basis of the induction of pathomorphosis of the tumor tissue of breast cancer.